(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Creative orientation to solve problems is gaining great importance in light of challenges posed by the continuing and rapid changes which taking place in the business environment in the present time. Where organizations tend to analyze the creative behavior of employees in order to identify their creative styles, and understand them more deeply and accurately, in order to direct them to achieve the maximum benefit from these creative energies. The research aims to evaluate the creative attitude of the employees in solving problems in the Commercial Bank of Syria in light of the crisis by using VIEW model. To achieve the objectives of the study three hypotheses has been formulated, and tested by the Statistical Package for Social Sciences SPSS V (23), The results showed that There is a good trend in the studied sample in the Commercial Bank of Syria towards the discovery, and intheir dependence on external sources to solve the problems. While there is medial and acceptable trend in following oriented -persons style when they make decisions. يكتسب التوجه الإبداعي لحل المشكلات، أهمية كبيرة في ظل التحديات التي تفرضها التغيرات المستمرة والمتسارعة التي تشهدها بيئة الأعمال في الوقت الراهن. حيث تتجه المنظمات إلى تحليل السلوك الإبداعي للعاملين بهدف التعرف على الأنماط الإبداعية الموجودة لديها وفهمها بشكل أعمق وأدق بهدف توجيهها بما يحقق الاستفادة القصوى من هذه الطاقات الإبداعية. يهدف البحث إلى تقييم التوجه الإبداعي لدى العاملين في حل المشكلات في المصرف التجاري السوري في ظل الأزمة باستخدام نموذج VIEW.ولتحقيق أهداف الدراسة تم صياغة ثلاث فرضيات، تم اختبارها بواسطة الحزمة الإحصائية للعلوم الاجتماعية Statistical Package for Social Sciences,SPSS V(23), وقد توصلت الباحثة إلى عدة نتائج أهمّها: يوجد توجه جيد لدى أفراد العينة المدروسة في المصرف التجاري السوري نحو الاكتشاف، ونحو اعتمادهم على مصادر خارجية في معالجة المشكلات. بينما يوجد توجه وسطي مقبول في اتباعهم أسلوب التوجه بالأشخاص عند اتخاذ القرارات.